Primary human hepatocytes are protected against complement by multiple regulators - Halme, Jarkko; Sachse, Michael; Vogel, Heiko; Giese, Thomas; Klar, Ernst; Kirschfink, Michael (Molecular immunology, 2009)
Inflammatory liver disorders are often associated with a potentially tissue damaging complement activation directly at the main site of complement protein synthesis. As hepatocytes may be the primary target of complement attack, we investigated the expression and protective capacity of soluble and membrane-bound complement regulatory proteins in primary human hepatocytes (PHH). Isolated PHHs were analyzed for their basal and cytokine-induced complement regulator expression by cytofluorometry, rtPCR, confocal laser microscopy and ELISA. Susceptibility to complement-mediated cell lysis was investigated with cytotoxicity tests. In contrast to previous reports, PHHs expressed CD46, CD55, CD59, soluble CD59 (sCD59) and factor H (fH), but not CD35. A low basal expression of CD55 was strongly enhanced by IFN-γ, IL-1β and TNF-α. The expression of CD59 could be augmented by IL-1β, IL-6 and TNF-α but was suppressed by IFN-γ. CD46 expression was not significantly altered. PHHs synthesized fH and sCD59 and fH was detected on PHH surface after exposure to IL-1β. Inhibition experiments revealed that CD59 was most effective in protecting PHHs from complement attack. These data clearly indicate that PHHs are protected by multiple complement regulatory proteins, which are controlled by proinflammatory cytokines. CD59 appears to be pivotal in protecting PHHs against complement-mediated lysis.
Gesehen am 04.12.2019